Measuring the vibration of a brush cutter in different operation modes - László, H. E. (International Journal of Horticultural Science, 2014)
The vibration load of a hand-held machine depends on many factors not defined in the ISO 5349:2001 standard about the measurements and evaluation of human exposure to hand-transmitted vibration. In this study, the effect of different operation modes on the vibration emission of a brush cutter was investigated. The frequency weighted r.m.s. acceleration was measured at the front (left) and rear (right) handle in three orthogonal directions according to ISO 5349 (2001). Two set of measurements were performed with three subjects for idling and cutting operations. In addition, the acceleration was measured with two holding positions, i.e. the cutting head is tilted by 45˚ to the left and tilted by 45˚ to the right. The standard vibration evaluation method, with the cutting head parallels to the ground, significantly under-estimated the vibration emission of the tilted tool to the left and right. The results suggest that the use of different holding positions would improve the reliability of the standard method of assessing the vibration of hand-held tools.